The impact of inflammation and iron metabolism on gene expression alterations in ischemic stroke: a bioinformatics approach - Shengwu Wang; Xuemei Li; Youcai Bi; Chao Yan; Yunbo Chen (Scientific Reports)
Abstract This study explores the differential expression of inflammation and iron metabolism-related genes (IIMRDEGs) in Ischemic Stroke (IS), a major contributor to global morbidity and mortality. Using the Gene Expression Omnibus (GEO) query tool, we integrated gene expression datasets GSE22255 and GSE16561. We identified 56 differentially expressed genes (DEGs), including 42 that were upregulated and 14 downregulated, according to criteria of |logFC| > 0.5 and p < 0.05. An intersection with known IIMRDEGs revealed 16 genes with significant relevance to IS, such as SLC22A4 and DUSP1. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses indicated that these genes are mainly involved in leukocyte chemotaxis and responses to bacterial molecules, in addition to IL-17 and TNF signaling pathways. A protein-protein interaction (PPI) network of 12 IIMRDEGs identified 8 hub genes, including IL7R and ADM, which exhibited significant expression differences (p < 0.001) and potential diagnostic utility with AUC values between 0.7 and 0.9 in ROC curve analysis. Furthermore, immune infiltration analysis showed notable differences in 7 immune cell types between IS and control samples. Our findings advance the understanding of ischemic stroke mechanisms and present potential biomarkers for improving diagnosis and therapeutic strategies.